Mengenali Depresi Anak Sejak Dini : Kajian Teoritis dan Implikasi Praktis - Agung Patrio Iksan; Aneti Vilva Fauziah; Setiawan Candra; Sri Mulyeni (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
The purpose of this study was to examine the phenomenon of depression in children with a focus on early identification, risk factors, and effective treatment approaches. The method used in this study was a narrative literature review that synthesized findings from various scientific journals, academic books, and reports from world health organizations related to depression in children. The results of the analysis indicate that depression in children is a real clinical condition but is often undiagnosed due to differences in symptoms compared to adults and lack of public awareness. The main risk factors include childhood trauma, genetics, and dysfunctional family dynamics. Evidence-based approaches such as cognitive-behavioral therapy (CBT), family therapy, and psychosocial interventions have shown effectiveness in reducing symptoms. The conclusion of this study emphasizes the importance of early detection and intervention as a preventive measure to minimize the long-term impact on children's mental health.